2002
DOI: 10.1067/mtc.2002.125647
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic image comparison between mediastinal and lung windows provides possible prognostic information in patients with small peripheral lung adenocarcinoma

Abstract: It is suggested that the ratio of the area of the mediastinal computed tomographic image to that of the lung computed tomographic image can be a prognostic factor in patients with small peripheral lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
2
8
0
1
Order By: Relevance
“…In patients with adenocarcinoma of the lung, particularly those with BAC components, this conventional T staging might be inappropriate. Our results confirm the Japanese studies which found that size measured on CT using an MW setting had better discrimination between absence or presence of nodal spread and prognostic value than size measured on an LW setting [9,25,26]. This can be explained by the fact that the LW incorporates both benign and aggressive elements of mixed adenocarcinomas.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In patients with adenocarcinoma of the lung, particularly those with BAC components, this conventional T staging might be inappropriate. Our results confirm the Japanese studies which found that size measured on CT using an MW setting had better discrimination between absence or presence of nodal spread and prognostic value than size measured on an LW setting [9,25,26]. This can be explained by the fact that the LW incorporates both benign and aggressive elements of mixed adenocarcinomas.…”
Section: Discussionsupporting
confidence: 88%
“…Alternative approaches using simpler radiological measurements of tumour size based on lung and softtissue windows [9], particularly the two-dimensional TDR [16][17][18][19] from which the mTDR in the current study is derived, correlate well with quantitative measurement of the degree of ground-glass appearance. These measurements are at least as good a prognostic indicator as the GGO-based methods [19].…”
Section: Ct-derived Tumour Size In Lung Cancermentioning
confidence: 69%
See 2 more Smart Citations
“…Two articles measured PSNs, one time using lung window settings only and the other time using both mediastinal and lung window settings [80, 81]; these two articles are included. Another four articles used only the approach using mediastinal and lung window settings and these four articles were excluded [46, 8284] because the mediastinal settings were not standardised and varied widely. In summary, 4 of the 31 studies were excluded, leaving 27 studies.…”
Section: Resultsmentioning
confidence: 99%